(untitled) (Bangladesh Journal of Agricultural Research, 2013)
Mungbean is a popular and widely grown pulse in Bangladesh. Coastal farmers are cultivating BARI-Mung varieties, but many farmers are still reluctant to adopt these improved varieties that need to be identified. Therefore, the study was conducted in three mungbean growing coastal districts, namely Barisal, Patuakhali, and Noakhali of Bangladesh during 2010-2011 to assess the extent of technology adoption and constraints to BARI-Mungbean production. The study focused the level of technology adoption in terms of variety use, input use and agronomic practices. The study revealed that farmers followed the recommended practices which were very encouraging. All the farmers adopted improved mungben varieties of which 51% farmers adopted BARI Mung-5 variety. The level of adoption of seed rate, use of urea, and MoP was found to be high. The level of adoption of agronomic practices like ploughing, sowing time, weeding and insecticides use were also found to be high. The farmers were mostly influenced by DAE personnel and neighboring farmers in adopting improved mungbean technology. Multiple regression revealed that experience, training, organizational membership, relation with different media, and mungbean suitable area had positive and significant influence in increasing the area under mungbean cultivation. Most farmers showed positive attitude towards improved mungbean cultivation of which 67% farmers wanted to increase its cultivation in the next year. The major constraints to improved mungbean production were high price of insecticides, lack of labour and disease and insect infestation. Farmers required improved mungbean seeds and production technology which may increase the yield and income of the farmers. Bangladesh J. Agril. Res. 38(1): 85-96, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15193